Desenvolvimento de membranas de alumina anódica porosa com nanopartículas de prata depositadas - Machado, Maria Manuela Pereira (2015)
In this work, we present the development of porous anodic alumina (PAA) membranes for ultrafiltration by the anodization of low cost 1050 aluminum (Al) foils (99.5% purity). The metallic Al and the barrier layer of alumina were removed by dissolution of a smaller area to support the membrane in the Al base. The membranes were characterized by field-emission scanning electron microscopy (FE-SEM) to measure the effective pore diameter and its thickness. Gas permeability measurements with N2 were performed to estimate the liquid flux using Darcy’s law and Forchheimer equations. For the 23 factorial design, three responses were studied: pore diameter, membrane thickness and liquid flux. We observed that the most import effects for obtaining an appropriate pore diameter were current density and electrolyte type, whereas to obtain a good liquid flux the most import factor was the interaction between the current density and electrolyte type. The second part of this work was the deposition of silver nanoparticles inside the porous of the PAA membranes. Escherichia coli, a common bacterial contamination of drinking water, was removed using these PAA membranes to obtain bacteria-free water for human consumption and a filtration retention of 100% was achieved, with or without the presence of silver nanoparticles, which adds the membranes, bactericidal effect.